Assessing Gender Differences in Consumer Perceptions and Attitudes Toward Post-harvest Losses of Fresh Produce in Anambra State, Nigeria - Belonwu, Chioma Peace; Mogbo, Anulika Gloria (P3M Politeknik Negeri Jember, 2026)
Post-harvest losses of fresh produce constitute a major but under-examined household-level problem in Nigeria, with limited empirical evidence on how consumer gender differences shape awareness, attitudes, behaviours, and loss-reduction strategies. This study addresses this gap by examining gender-based variations in consumer responses to post-harvest losses in Anambra State, Nigeria. Using a descriptive survey design, data were collected from 116 purposively selected consumers actively involved in the purchase, storage, and management of fresh produce across urban, semi-urban, and rural locations. A structured 4-point Likert-scale questionnaire was administered online via Google Forms. The instrument was validated by subject-matter experts and demonstrated strong reliability (Cronbach’s alpha = 0.85). Descriptive statistics and Kruskal–Wallis tests were employed to examine gender differences in awareness, attitudes, behaviours, and household strategies at p ≤ .05. Findings revealed clear gender-based patterns. Although females showed higher awareness of post-harvest losses than males, the difference was not statistically significant (χ² = 2.802; p = .094). However, significant gender differences were observed in attitudes and household strategies, with females demonstrating more positive attitudes and stronger loss-reduction strategies than males (χ² = 11.902; p = .001). Consumer behaviours did not differ significantly by gender, despite males recording slightly higher mean ranks (χ² = 1.910; p = .167). The novelty of this study lies in its household-level, gender-disaggregated analysis of consumer responses to post-harvest losses, an area often overlooked in Nigerian food loss research that predominantly focuses on production and supply chains. The findings underscore the importance of gender-responsive consumer education and behavioural interventions. From a policy perspective, targeted awareness campaigns and household-focused loss-reduction programs, particularly those strengthening male engagement and reinforcing effective female-led strategies, could contribute meaningfully to reducing post-harvest losses and improving food security.